Nelson T. Johnson papers - Johnson, Nelson T. (Nelson Trusler), 1887-1954.
Correspondence, memoranda of conversations, speeches, writings, engagement books, and other papers relating to Johnson's diplomatic service with the U.S. Dept. of State in Australia, China, and East Asia, including his years as ambassador to China and secretary general of the Far Eastern Commission. Subjects include China during the early phase of the civil war between the Communist (Zhongguo gong chan dang) and Kuomintang (Zhongguo guo min dang) parties, the Japanese invasion of Manchuria in 1931, the Sino-Japanese War (1937-1945), and Australia during World War II. Correspondents include Edwin Sheddan Cunningham; John Foster Dulles; Joseph C. Grew; Stanley Kuhl Hornbeck; Roy Wilson Howard; Cordell Hull; Miles Lampson, Baron Killearn; Thomas W. Lamont; Owen Lattimore; Henry Morgenthau (1891-1967); and Francis Bowes Sayre.
U.S. assistant secretary of state, minister and ambassador to China, and minister to Australia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cunningham, Edwin Sheddan, -- 1868-1953 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Hornbeck, Stanley Kuhl, -- 1883-1966 -- Correspondence; Howard, Roy Wilson, -- 1883-1964 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Killearn, Miles Lampson, -- Baron, -- 1880-1964 -- Correspondence; Lattimore, Owen, -- 1900-1989 -- Correspondence; Lamont, Thomas W. -- 1870-1948 -- Correspondence; Morgenthau, Henry, -- 1891-1967 -- Correspondence; Sayre, Francis Bowes, -- 1885-1972 -- Correspondence; United States. -- Department of State; Far Eastern Commission; Zhongguo gong chan dang; Zhongguo guo min dang; Communism -- China; Diplomatic and consular service, American -- Australia; Diplomatic and consular service, American -- China; Diplomatic and consular service, American -- East Asia; Japanese -- China -- Manchuria; Sino-Japanese Conflict, 1931-1933.; Sino-Japanese War, 1937-1945.; World War, 1939-1945 -- Australia; Australia -- Foreign relations -- United States; China -- Foreign relations -- United States; China -- History -- Republic, 1912-1949.; East Asia -- Foreign relations -- United States; Japan -- History -- 1926-1945.; Manchuria (China) -- History; United States -- Foreign relations -- Australia; United States -- Foreign relations -- China; United States -- Foreign relations -- East Asia; Diplomats; Public officials